Experience of allergen-specific immunotherapy in the patient with oral and systemic manifestations of birch pollen allergy - E. Y. Trushina; E. M. Kostina; E. A. Orlova; A. A. Turovskaya; T. A. Nefedova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2024)
Introduction. Allergy to birch pollen is a common allergic disease. The main allergen of birch pollen is Bet v 1. The Bet v 1 protein structure is the similar to proteins of hazel, alder and elm pollen, as well as fruits proteins (apples, apricots, peaches, cherries) and vegetables ones (carrots, celery). Therefore, children with an allergy to the Bet v 1 protein may experience oral allergy syndrome (OAS) and even anaphylaxis when eating these foods. Allergen-specific immunotherapy (ASIT) is the indication for the pollen allergy treatment.Presentation of the clinical case. A 11 years old child was observed with a diagnosis of bronchial asthma, allergic form, moderate persistent clinical course. Pollinosis. Allergic rhinitis. Allergic conjunctivitis. Allergy to birch pollen (Bet v 1). Cross food hypersensitivity: oral syndrome (PR-10 proteins) and anaphylaxis (hazelnuts, peanuts). Systemic manifestations of pollen allergy limit immunotherapy due to the possible development of adverse reactions.The child was prescribed sublingual immunotherapy (SLIT) with the medication "Staloral birch pollen allergen". Baseline therapy was chosen for the child to achieve control of asthma and rhinitis, a hypoallergenic diet with the exclusion of significant food allergens was prescribed. Asthma and rhinitis exacerbation and OAS was observed during the 1st and 2nd treatment courses. Against the background of baseline therapy, SLIT was continued. The full maintenance dose was achieved during the 3rd SLIT course. Immunotherapy contributed to the reduction of symptoms of rhinitis and asthma, reduction of disease clinical course severity, reduction of baseline medications doses and OAS relief.